Financial Report Preparation Training For Kendari City MSMEs - Supriyadi, Supriyadi; Hasnita, Nita; Hasidin, Mirza Hapsari; Limbong, Diamond; Prabu, Zaga Raditya; Lestari, Puji (CARE: Journal Pengabdian Multi Disiplin, 2024)
This service aims to improve UMKM's understanding and skills in preparing financial reports following applicable accounting standards. This training provides a deeper understanding of the importance of accurate and transparent financial reports and how to implement SAK EMKM in daily practice. From the results of the training, it can be concluded that several points regarding the training participants showed an increased understanding of SAK EMKM and the importance of financial reports that comply with standards. Practical training technical skills which helped participants develop technical skills in preparing financial reports. However, some participants still needed further assistance, and access to financing with better financial reports, it is hoped that UMKM can more easily access funding from financial institutions and participants' awareness and motivation of the importance of good financial management will increase, which is reflected in active participation and enthusiasm in training sessions. However, several challenges are still faced, such as limited training time which means the material cannot be absorbed optimally by all participants, and the need for further assistance to ensure consistent implementation of SAK EMKM.